New forms of induction of apoptosis in aggressive lymphoma using peptides that interrupt the RAS / RAF interaction - Bergna, Cecilia (2019)
RAS-RAF-MEK-ERK is a key pathway for apoptosis regulation in cancer cells. B-Raf-inhibitors such as PLX4032 peptide was developed by Institute Curie-Université Pierre et Marie Curie in order to induce apoptosis in cancer cells. Objective: To demonstrate pro-apoptotic properties and survival outcome of EP2014/064243 peptide in murine aggressive lymphoma. Material and methods: BALBc mice with T-lymphoma were randomized assigned either in Group A (peptide+cyclophosphamide-CFM); Group B (peptides), Group C (CFM-control) or Control D (Cl-Na 0.9%-SF control group). Survival probability was calculated by Kaplan-Meier analysis. Apoptosis was detected using TUNEL technique. The protocol was approved by the Institutional Committee for Animal Care (CICUAL: T04-01-2015). Results: The median survival was 24 days (21.6-26.4) for placebo, 33 days (28.0-35.4) for the CFM monotherapy group, 33 (27.1-35.8) for the peptide group and 34 days (24,4-40) for CFM-peptide combined treatment (p < 0.05). In lymph node tissue the mean TUNEL positive cells per field for each treatment group was 2, 12 and 13 and 35 for SF, CFM, peptide and combined therapy (p < 0.05). Conclusion: These findings suggest that in murine aggressive lymphoma treated by an experimental peptide in addition with CFM, had an exponentially pro-apoptotic effect than CFM alone, suggesting that the peptide potentiated the anti-tumoural effect of CFM.